CHEMICAL INDUSTRY OF THE REGIONS OF UKRAINE: ASSESSMENT OF THE DYNAMICS OF DEVELOPMENT AND EFFICIENCY OF FUNCTIONING (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The chemical industry is one of the key export-oriented sectors of the national economy. Given the intensification of the processes of globalization and competition in the global market for chemical products, this sector of the domestic industry needs in-depth assessments at the regional level. The purpose of the article is to group the regions of Ukraine by the level of potential, dynamics of development and efficiency of the functioning of the chemical industry. For realization of the set tasks the calculation and estimation of the set of indicators, which reflect: the growth rate of the volume of chemical products sold and the share of exports in it, as well as labor productivity, operating profitability, financial result (balance) and the share of profitable enterprises of the chemical industry of the regions of Ukraine. Based on the dynamics of the values of the main performance indicators and economic efficiency of the chemical industry in 2017, the regions of Ukraine are conditionally divided into 4 groups: group 1 – regions with significant potential and high efficiency (Dnipropetrovsk, Kyiv, Kharkiv, Poltava and Vinnytsia regions); group 2 – regions with significant potential, but low efficiency (Cherkasy, Ivano-Frankivsk, Zaporozhye, Sumy, Rivne, Donetsk, Lugansk and Odessa regions); group 3 – regions with insignificant potential, but high level of efficiency (Lviv, Zakarpattia, Zhytomyr, Mykolayiv and Kherson regions); group 4 – regions with insignificant potential and low efficiency (Ternopil, Kirovograd, Chernihiv, Khmelnytsky, Volyn and Chernivtsi regions). The complex of measures aimed at increasing the export potential of domestic chemical production, which in particular, provides for stimulation of export activity of enterprises and their technical re-equipment, as well as the creation of new high-tech industries and the implementation of infrastructure projects in the regions of Ukraine, is proposed.
Keywords: chemical industry, production, sales volumes of chemical products, efficiency, export.